Sustainable Requalification of the Zeferino Vaz Campus Drainage System: Nature-Based Solutions for Climate Resilience - Romero, Gabriela Marques; Dalbelo, Thalita S. (Universitas Diponegoro, 2025)
The increasing impermeabilization of soil and intensification of extreme weather events have heightened the risk of flooding at Unicamp's Zeferino Vaz campus. Designed in the 1960s, the current drainage infrastructure is no longer adequate to meet present and future climate challenges. This study proposes the requalification of the drainage system through Nature-Based Solutions (NbS), aligning with Unicamp’s 2021-2031 Integrated Territorial Master Plan and the United Nations Sustainable Development Goals (SDGs). NbS promote a shift from traditional rapid runoff models to sustainable drainage strategies that enhance infiltration, evapotranspiration, and retention. The project adopts a multi-scalar methodology, integrating interventions at the lot, street, neighborhood, and watershed levels. Planning is structured into five steps: hydrological diagnosis, mapping of impermeable and flood-prone areas, typology selection, feasibility analysis, and integration into institutional planning. The project is currently in its third step, identifying suitable NbS typologies for priority zones on campus. Supported by Unicamp’s sustainability governance, the initiative is embedded in a broader data-driven and participatory approach. It also foresees the integration of educational components, monitoring systems, and partnerships with academic and municipal stakeholders. Preliminary results include a complete hydrological diagnosis, detailed geospatial mapping of impermeable and flood-prone areas, and the preliminary selection of NbS typologies tailored to priority campus zones. The expected outcomes include flood risk reduction, increased biodiversity, enhanced thermal comfort, and the creation of outdoor learning environments. By leveraging its living lab model and long-standing sustainability commitment, Unicamp aims to transform environmental challenges into opportunities for innovation and resilience, and offers a replicable model for universities and urban areas.